Luxembourg : Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2010)
The staff report for the 2010 Article IV Consultation underlies a thorough and objective view of the macroeconomic situation in Luxembourg and the challenges the economy is facing. The country's enviable position of public finances at the onset of the crisis provided the space to accommodate fiscal support to the economy, enhance social transfers, and protect household income. Executive Directors recommended a sharper focus on liquidity and credit risks arising from banks' sizable and concentrated exposures to their foreign parent groups.